Carrier-free subunit nanovaccine amplifies immune responses against tumors and viral infections. (1st March 2023) - Chen, Haolin; Li, Yuhui; Li, Liyan; Yang, Zeyu; Wen, Zhenfu; Liu, Lixin; Liu, Hong; Chen, Yongming
Abstract: Codelivering subunit antigens and Toll-like receptor (TLR) molecular adjuvants via nanocarriers can stimulate potent innate and specific immune responses. Simple and effective nanovaccines fabrication is crucial for application. However, most nanovaccines were fabricated by introducing additional delivery materials, increasing safety risk, cost and processing complexity. Herein, a carrier-free nanovaccine was facilely prepared using a TLR1/TLR2 adjuvant, Diprovocim, rich in benzene rings that could interact with aromatic residues in subunit antigens through π-π stacking without additional materials. The carrier-free nanovaccines with a narrow size distribution could target lymph nodes (LNs) after intravenous injection to mice. The carrier-free nanovaccines based on ovalbumin (OVA) can stimulate strong antibody titers and CD4 + and CD8 + T cell immune responses in mice, and it synergized with anti-PD1 showing a potent tumor suppression in B16F10-OVA tumor model of mice. Furthermore, the carrier-free nanovaccine with glycoprotein E (gE), a glycoprotein of the varicella-zoster virus (VZV), also showed potent humoral and cellular immune responses. Therefore, using subunit proteins to support Diprovocim by π-π stacking provides a new approach for the preparation and application of novel vaccines for tumor therapy and prevention of infectious diseases. Statement of significance: Codelivering subunit antigens and adjuvants via nanocarriers stimulate potent innate and specific immune responses. However, existing delivery materials for fabricating nanovaccines will inevitably increase the cost of preparation, controllability, process complexity and safety assessment. Therefore, this study easily prepared carrier-free nanovaccines using the benzene ring-rich TLR1/TLR2 adjuvant Diprovocim, which can interact with aromatic residues in subunit antigens via π-π stacking without additional materials. The carrier-free nanovaccines of OVA demonstrated a potent tumor inhibition in treating melanoma in combination with anti-PD1. And the nanovaccines of gE stimulated a strong antibody titer and cellular immune response for herpes zoster. Thus, the present study provides a new approach for the preparation of subunit vaccines to combat various cancers and virus infections. Graphical abstract: Image, graphical abstract